Evaluation of the peak experience scale as a rapid assessment tool for the strength of a psychoactive experience with 5-MeO-DMT - Reckweg, Johannes T.; Mason, Natasha L.; Theunissen, Eef L.; Svendsen, Claus B.; Terwey, Theis H.; Ramaekers, Johannes G. (Frontiers in Psychology, 2025)
A three-item Peak Experience Scale (PES) was developed to rapidly evaluate the strength of the psychoactive experience, and to guide the dosing regimen, of the psychedelic 5-methoxy-N,N-dimethyltryptamine (5-MeO-DMT; mebufotenin). This paper aims to compare the PES with a range of established questionnaires designed to evaluate the psychedelic experience. Data were gathered from three separate studies in which a 5-MeO-DMT formulation (GH001) was administered via pulmonary inhalation to healthy volunteers and patients with treatment resistant depression (N = 84) as either single doses (0 [placebo], 2, 6, 12, 18 mg) or an incremental individualized dosing regimen (IDR). Apart from the PES, participants also completed the Mystical Experience Questionnaire (MEQ-30), the Challenging Experience Questionnaire (CEQ), the Ego Dissolution Inventory (EDI) and the 5-Dimensional Altered States of Consciousness Rating Scale (5D-ASC). The 5-MeO-DMT formulation produced a significant, dose-related increase in PES ratings, with maximal ratings being achieved after the IDR. A principal component analysis (PCA) of the PES items identified a single primary component explaining 83.5% of the variance. PES items also displayed a strong internal consistency (Cronbach’s α = 0.896). A PCA across all questionnaires indicated a strong and unidimensional loading of the PES, MEQ, EDI and the 5D-ASC, suggesting high interrelatedness. Likewise, individual ratings on the PES were highly correlated to those on the PES, MEQ, EDI and the 5D-ASC, but not the CEQ. The PES is concluded to be an effective tool to rapidly assess the strength of the psychedelic experience with 5-MeO-DMT. The PES could prove useful to gain fast insight into the strength of a psychedelic dose in individual patients and potentially guide dose and re-dose selection of rapid-acting psychedelics.